Dose rates and seasonal variations of 238U, 232Th, 226Ra 40K and 137Cs radionuclides in soils along Thrace, Turkey - Akozcan, Serpil; Yilmaz, Mucahit; Kulahci, Fatih (Springer, 2014)
Concentrations of U-238, Th-232, Ra-226, K-40 and Cs-137 are measured in collected soil samples from various locations in the Thrace region of Turkey. The activity concentrations range from 12.82 to 101.75 Bq kg(-1) d.w. (dry weight) for U-238, from 5.16 to 73.34 Bq kg(-1) d.w. for Th-232, from 185.54 to 5399 Bq kg(-1) d.w. for K-40 and from 11.42 to 90.73 Bq kg(-1) d.w. for Ra-226. In addition to naturally occurring radionuclides, Cs-137 activity concentration is determined between 3.05 and 46.78 Bq kg(-1) d.w. for soil samples. Determination of the radiological hazard is achieved through calculations of the external terrestrial gamma dose rate in air (nGy h(-1)) and annual effective dose rate (mSv year(-1)) and the results are compared with the similar works in different countries.
Keywords: Natural radionuclide; Uranium; Thorium; Radium; Cesium; Potassium; Soil